Characterisation of the non-starter bacterial flora of Stilton cheese - Mugampoza, Diriisa (2013)
This study characterised the bacterial flora of a commercially produced Stilton cheese in an effort to determine the contribution of non-starter lactic acid bacteria (NSLAB) to its aroma profile. A total of 123 microbial strains previously isolated from different sites (outer crust, blue veins and white core) of the cheese sample obtained at the end of ripening (~8 weeks) were recovered in MRS and BHI broths and preliminarily identified using conventional microbiological methods in order to establish population diversity and to screen out yeasts and moulds. Organisms identified with partial 16S rDNA sequence analysis were Lactobacillus plantarum, Lactobacillus brevis, Enterococcus faecalis, Staphylococcus aureus, Acinetobacter baumanii and Psychrobacter spp., with the genus Lactobacillus being the dominant (75%) group detected in all the sampled sites. Cluster analysis of pulse-field gel electrophoresis patterns associated the Lactobacillus isolates according to their site of isolation.